Assessing the Nutritional Status of Children with Leukemia from Hospitals in Kuala Lumpur - Abu Zaid, Zalina; Shahar, Suzana; A. Jamal, A. Rahman; Mohd Yusoff, Noor Aini (Nutrition Society of Malaysia, 2009)
A cross-sectional study was carried out to evaluate the nutritional status of 51 subjects with leukemia aged 4 to 12 years from the Haematology & Oncology Paediatric Ward, Universiti Kebangsaan Malaysia Medical Centre (PPUKM) and the Paediatric Institute of Kuala Lumpur. Nutritional status was assessed using anthropometric measurements, biochemical and haematological parameters. Subjects comprised 32 (62.7%) males and 19 (27.3%) females. Most of the subjects (41.2%) were in the age group of 4 to 6 years. More than half of the children were Malays (70.6%) followed by Indians (15.7%) and Chinese (13.7%). The subjects were diagnosed as acute lymphoblastic leukemia (ALL) (84.3%) followed by acute myelogenous leukemia (AML) (13.7%) and chronic myelogenous leukemia (CML) (2.0%) respectively. Most of the children were in remission status (54.9%). Underweight (<-2 SD for weight-for-age) was observed in 37.3% of the children while 17.6% of them were stunted (<-2 SD for height-for-age), and sign(s) of malnutrition (<-2 SD) for mid upper arm circumference (MUAC)-for-age was observed in 15.7% of the subjects. Approximately 20.0% of the subjects were in the severe malnutrition category with respect to low serum albumin levels (<3.5g/dl). All subjects had hemoglobin levels of less than the normal range. While the results indicated no significant differences in the nutritional status of subjects with leukemia at different stages of treatment, it was observed that the prevalence of malnutrition was higher in children with newly diagnosed leukemia. Thus, the nutritional status of children with leukemia should be monitored closely as there is a likelihood of deterioration owing to the disease.